Adherence and Drug Related Problems to Antiretroviral Medication among HIV/AIDS Patients in Buengkan Hospital - Seanglam, Nantana (Journal of Preventive Medicine Association of Thailand, 2020)
This study was to investigated Adherence and drug related problems to antiretroviral medication among HIV/AIDS patients in Buengkan Hospital. This study is prospective study. The data were collected during the period from February 2017 to May 2017, 200 patients with random sampling. The result of the study showed that patients who received antiretroviral treatment were female about 51.50% and male about 48.50% most were between 40-49 years and 30-39 years, 47.50% and 34.50%, respectively, have a CD4 cells<500 cell/mm3 59.00% and a Viral load=0 copy 70.50%. The sample about 67.50% had very good adherence and good adherence about 25.00%. Most of the non-adherence in drug use miss time over 30 minute (79.44%) and forgetfulness of medication lead to lack of medication, lack of medication (6.54%, 6.54%). Found drug related problems, 5.50% majority was due to the absence of medication to be treated and adverse drug reactions (2.00% and 2.00%). And found that the age group 35 years had adherence, which was higher than the age <35 years group with statistical significance (p=0.013) And found that the viral load 50 copy group had higher adherence than the viral load > 50 copy group with statistical significance (p=0.013). The conclusion, This study was used to provide a multidisciplinary team of caregivers. Providing advice will allow patients to collaborate more on medication and reduce the problem of long-term resistance. It is better.